Mathematical analysis of energies for viscoelastic materials and energy based failure criteria for creep loading - Rui Miranda Guedes (2004)
In this work energy based failure criteria are applied and assessed using published experimental data. Reiner and Weissenberg (R-W) developed an energy failure criterion based on deviatoric free energy. In this theoretical model, failure is part of the complete constitutive description of the material. Some considerations are given to the energy for viscoelastic materials characterized by single-integrals. Some studies show that for materials with memory there is more than one free energy compatible with the thermodynamical principles. The free energy is defined and related to the viscoelastic model. Failure criteria are defined and tested for some polymers and FRP. The experimental data of some materials, at room and elevated temperatures, reveals some discrepancies with R-W criterion and a criterion modification is proposed. It is concluded that the R-W criterion is not universal.